Love, loss, and existential despair: The fragile relationships in Haruki Murakami’s Norwegian wood - Uzma, Sidratul Muntaha; Hasan, A. M. M. Mahmudul; Rouf, Prof. Dr. Md. Abdur (Yayasan Mitra Persada Nusantara, 2025)
Against the backdrop of 1960s Japan, Haruki Murakami's novel Norwegian Wood examines the complex dynamics of broken relationships, emotional alienation, and existential crises. This article focuses at how the protagonists in the novel—Toru Watanabe, Naoko, Midori, Reiko, Nagasawa and Hatsumi manage their relationships while confronting personal traumas, identity crises, and meaning seeking in a shattered society. Inspired by existentialist notions from Jean-Paul Sartre, Søren Kierkegaard, Zygmunt Bauman, Albert Camus, and Simone de Beauvoir, this research looks at issues of loneliness, bereavement, ambiguous morality, and emotional paralysis. The study stresses Murakami's use of fractured narrative and retroactive storytelling to show the intricacy of human connection by way of a qualitative literary analysis including textual and character development analysis. Fundamentally, Norwegian Wood presents a remarkable commentary on the existential dilemmas of modern living, in which humans strive between desire and detachment, commitment and freedom, past and present, in an uncaring world.